Fast terminal sliding mode tracking control of nonlinear uncertain mass–spring system with experimental verifications. (4th February 2019) - Amirkhani, Saeed; Mobayen, Saleh; Iliaee, Nahal; Boubaker, Olfa; Hosseinnia, S Hassan
In this article, a fast terminal sliding mode control technique is used for robust tracking control of a nonlinear uncertain mass–spring system in the existence of external perturbation. This system is considered as a benchmark problem in the flexible joint mechanisms. The joints flexibility in the robotic systems creates one of the most significant sources of parametric uncertainties. The theory of Lyapunov stability is used for the formulation of the proposed control method, and the presence of the sliding around the switching surface is satisfied in the finite time. Simulation results as well as the experimental verifications prove the efficiency and applicability of the suggested approach in the presence of parametric uncertainty, noise, and exterior disturbance.